Evaluating different hermetic storage technologies to arrest mold growth, prevent mycotoxin accumulation and preserve germination quality of stored chickpea in Ethiopia. (January 2020) - Alemayehu, Samuel; Abay, Fetien; Ayimut, Kiros Meles; Assefa, Dereje; Chala, Alemayehu; Mahroof, Rizana; Harvey, Jagger; Subramanyam, Bhadriraju
Abstract: Chickpea is an economically important pulse produced by millions of smallholder farmers as a source of food, income and nutrition in Ethiopia. Mold infection and mycotoxin production can potentially lead to significant losses of chickpea during storage. Under laboratory conditions we tested comparative effects of hermetic and traditional storage structures on mold infection, germination and mycotoxin levels of chickpea. Purdue Improved Crop Storage (PICS) bags, Super GrainPro (SGP) bags, and small metal bins were compared to the traditional and popularly used chickpea storage structures such as polypropylene (PP) bags and jute bags over a six-month storage period. Oxygen and carbon dioxide levels, chickpea temperature and moisture, seed infection with molds and percentage germination and mycotoxins levels were determined every two months for six months. In PICS bags, SGP bags and metal bins chickpea temperature and moisture changed very little during storage, whereas in jute and PP bags significant temperature and moisture increases were observed. Oxygen levels in PICS and SGP bags decreased from 20% to 8–10% in six months and carbon dioxide levels increased from 0.4% to 10% in PICS bags and from 0.1% to 17% in SGP bags. In jute and PP bags, oxygen levels were around 20% but carbon dioxide levels increased from 0.05% to 0.1–0.2%, perhaps due to mold activity. Mold infection decreased over time in chickpea stored in PICS bags, SGP bags, and metal bins, and seed germination was high (82–92%). Mold infection increased and seed germination decreased in chickpea stored in jute and PP bags. Increases in levels of aflatoxin, fumonisin, deoxynevalenol, and ochratoxin were observed only for chickpea stored in metal bins, and in jute and PP bags. Our study showed that PICS and SGP bags can effectively arrest mold growth, mycotoxin accumulation and preserve germination of chickpea during six months of storage. Highlights: Chickpea production is hampered by poor storage practices and facilities, which lead to contamination by spoilage fungi. PICS and SGP hermetic bags arrest fungal contamination and mycotoxin accumulation. During the six months period, the concentration of O2 in the hermetic bags dropped, while CO2 levels increased. Increased mycotoxin content was recorded for most of the storage treatments during the 6-month storage period. A PICS and SGP effectively arrested fungal infection and preserved germination of chickpea.